Des-Gamma-Carboxyprothrombin (PIVKA II) and Plasma Vitamin K1 in Newborns and Their Mothers - von Kries, R; Shearer, M J; Widdershoven, J; Motohara, K; Umbach, G; Göbel, U (Thrombosis and Haemostasis, 1992)
Assessments of the vitamin K status in newborns and their mothers by means of des-γ-carboxy-prothrombin (PIVKA II) measurement have given equivocal results. Part of the variability could be attributed to differences in sensitivity (i.e. the ability to detect small concentrations) and validity (i.e. ability to detect vitamin K deficiency) of the methods applied. None of these methods have yet been validated with respect to plasma vitamin K1. In 22 healthy mother/infant pairs PIVKA II was determined using three different assays including ratio Xa/ecarin (Xa/ec), crossed immunoelectrophoresis (CIE), and an ELISA with a monoclonal antibody (MAB). The results were compared with conventional clotting tests and plasma vitamin K1. The following results were obtained:Cord blood: Clotting tests within age-related normal ranges; PIVKA II detection rates: 0/22 (Xa/ec), 1/22 (CIE), 4/22 (MAB); plasma vitamin K1: undetectable in 20/22.Mothers: Clotting tests all within normal range; PIVKA II detection rates: 1/22 (Xa/ec), 0/22 (CIE), 5/22 (MAB); plasma vitamin K1 (pg/ml) for all mothers (median; range): 186; 55–833; for PIVKA II positive mothers: 213; 59–699.PIVKA II detectability in newborns and mothers was not correlated. The results show an increase in sensitivity for PIVKA II detection in the order of MAB ≫CIE >Xa/ec. Due to the very low plasma vitamin K1 at birth, no correlation was possible between cord PIVKA II detectability and plasma vitamin K1. However, in mothers at term PIVKA II MAB appears to be unrelated to the vitamin K status.